Sosialisasi Digital Marketing Berbasis Media Sosial bagi Siswa SMK Tunas Karya - Hasdiana, Hasdiana; Dewi, Arie Rafika; Sinaga, Tantri Hidayati; Sembiring, Boni Oktaviana; Rahayu, Eka (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2025)
Vocational High School (SMK) graduates are prepared to enter the workforce. It is essential for every SMK graduate to possess specialized skills to support their future career development. In the culinary arts program, for instance, students can leverage digital marketing techniques through social media platforms to market their products. Recognizing the significance of social media utilization, particularly Instagram, as a medium for business information and promotion, there is a need for digital marketing literacy among SMK Tunas Karya students. This Community Service Program (PkM) aims to enhance students' competencies in managing social media for digital business marketing. Through socialization and training initiatives, students are expected to comprehend digital marketing strategies via Instagram to support business activities. The program's success indicators include improved student understanding of Instagram usage as a communication medium and business promotion platform, as well as enhanced student proficiency in managing and presenting content creatively. Through the implementation of social media-based digital marketing strategies, students can expand their business reach, facilitate transactions, and increase profitability.